Nomenclatural standards of oat (Avena sativa L.) cultivars released by the Research Institute of Agriculture for the Northern Trans-Ural Region - M. N. Fomina; Yu. S. Ivanova; N. V. Lebedeva; I. V. Varganova (Труды по прикладной ботанике, генетике и селекции, 2025)
Background. Preparation and publication of the nomenclatural standard is an important step in a cultivar’s documenting. Development of nomenclatural standards for cultivars of domestic breeding helps to make and maintain a national catalog of valuable crop genetic resources.Materials and methods. Biomorphological and agronomic plant characters are described for the spring oat cultivars ‘Foma’, ‘Tobolyak’ and ‘Raduzhny’ developed at the Research Institute of Agriculture for the Northern Trans-Ural Region, branch of the Tyumen Scientific Center, Tyumen Province, Russia. Nomenclatural standards for these cultivars are presented. The plant material for the nomenclatural standards was collected at the experimental plots of Pushkin and Pavlovsk Laboratories of VIR. All plants of each cultivar were grown for the herbarium from a single seed sample. Each herbarium sheet contains an entire plant in the milk-ripeness stage, mature spikes, and grains samples.Results and conclusion. The nomenclatural standards were made in accordance with the recommendations of the International Code of Nomenclature for Cultivated Plants (ICNCP) and registered in the VIR Herbarium Database. The herbarium specimens are deposited with the Herbarium of Cultivated Plants of the World, Their Wild Relatives, and Weeds (WIR) at the National Center for Plant Genetic Resources. The nomenclatural standard for each cultivar is presented on one herbarium sheet, with three (‘Tobolyak’ and ‘Raduzhny’) or four (‘Foma’) duplicate sheets.